CD4+ T lymphocyte recovery in the modern antiretroviral therapy era: Toward a new threshold for defining immunological non-responders - Taramasso, Lucia; Labate, Laura; Briano, Federica; Brucci, Giorgia; Mora, Sara; Blanchi, Sabrina; Giacomini, Mauro; Bassetti, Matteo; Di Biagio, Antonio (Frontiers in Virology, 2023)
Despite the high efficacy of modern antiretroviral therapy (ART) in reducing HIV viremia and control viral replication, some people living with HIV (PLWH) do not recover CD4+ T cell count. To evaluate the frequency and predictive factors of discordant immune responses, we performed a retrospective cohort study of 324 antiretroviral-naive PLWH who initiated first line ART between 2008 and 2018 and maintained HIV-RNA<50 copies/mL during 36 months of follow up. PLWH were defined immunological non responders when CD4-T cell recovery was <20% compared to baseline (INR20%), or <500 (INR500) or <200 (INR200) cells/mm3 at 36 months. The prevalence of INR20%, INR500 and INR200 was 12.5%, 34.6% and 1.5%. After adjustment for possible confounders, CD4 nadir showed a significant association with all INR definitions, with lower values predicting INR500 (aOR 0.98, 95%CI 0.98-0.99, p <0.001) and INR200 (aOR 0.98, 95%CI 0.95-1.01, p= 0.096). Moreover, a higher baseline CD4/CD8 ratio was inversely related to the probability of being INR500 (OR 0.03, 95%CI 0.01-0.12, p<0.001) and INR200 (OR 0.002, 95%CI 18-7-67.72, p= 0.255). In contrast, INR20% had higher CD4 nadir and CD4/CD8 ratio compared to others, suggesting the identification of an heterogenous population with such definition. The present study highlights how INR200 have become rare in the contemporary ART era, whilst still about one third of PLWH meet criteria for INR500. Overcoming the threshold of 500 CD4/mm3 could be an appropriate definition of immune response, in contrast with the older definitions of INR200 and INR20%. Early diagnosis and rapid treatment initiation, before CD4 counts and CD4/CD8 ratio begin to decline, are critical for achieving an optimal immune response.